Reputation in Higher Education: A Systematic Review - Amado Mateus, Marelby; Juarez Acosta, Fernando (Frontiers in Education, 2022)
Published research on corporate reputation has increased in the last 10 years in various sectors. The higher education sector is no stranger to this growth; however, theoretical developments and empirical research have been conducted across various disciplines of knowledge and theoretical approaches, which has made it difficult to theorize about it. In addition to this, the dimensionality of the construct, its dependence on the perception of public interest, and the difficulty of its measurement have made it a challenge for universities. This article develops a systematic review of reputation in higher education institutions. While there is evidence of contributions in the development of the theory and its conceptualization, these have occurred in other organizational environments, and are not specifically focused on the higher education sector. As such, we seek to identify and characterize how reputation has been studied in this sector, highlighting conceptual and theoretical approaches that have supported the studies, which will help to overcome the fragmentation of the same from an integral definition applied to the education service.